Disabled services in Turkish university libraries: Istanbul University Central Library: The project of “Information Center for (dis)abilities” - Konya, Umit; Cihan, Figen; Bayrak, Özlem (Qualitative and Quantitative Methods in Libraries, 2017)
Following the establishment of Grand National Assembly of Turkey (23 April 1920) and the declaration of Turkish Republic (29 October 1923), the library, known as Darülfünun, began to be called Istanbul University Central Library with University Reform which took place in 1933. The collection of the Central Library of Istanbul University contains manuscripts dated as old as the 15th century in both Turkish and foreign languages. Once included within the scope of the Printed Texts and Picture Collection Law in 1934, it began gathering all the printed works published within the borders of Turkish Republic. And also with the Higher Education law no 2547 enacted in 1982, Central Library began operating under the name of Istanbul University, Office of Library and Documentation along with other libraries of faculty, department, institute and research centers. The library has still been offering services for users with its about 2 million documents.  By founding Information Center for (Dis)abilities on the understanding of a “university and a library accessible for all users” and on the basis of creating “capable disabled users”, Istanbul University Central Library has shown once more its modern approach to this issue. The Project has been carried out in collaboration with Istanbul University Office of Library and Documentation, Istanbul University Office of Health, Culture and Sports and Istanbul University Research and Implementation Center for Disabled People. In the Center, there are ten desktop computers with screen readers and with screen magnifier softwares for the people with low vision, a Braille printer for visually impaired students and researchers to convert written materials on digital environment to Braille, six Braille monitors, two reading cabinets to convert  printed books to audio books, two Braille printers for visually impaired students studying basic sciences and social sciences to print images and graphics. Three book reading machines that allow to capture printed documents and to playback them with a synthesized computer voice, three digital mouse for those who can’t use their body functions properly. Information center for (dis)abilities has filled a significant gap together with the one operating in Boğaziçi University.